Perception of Threat of Avian Influenza by Agricultural Extension Professionals and Poultry Farmers in Nigeria - Udoh, Augustine J.; Oku, Ene (International Journal of Poultry Science, 2010)
Avian influenza has become a serious threat in poultry farming in recent times in Nigeria. A study was undertaken to ascertain the perception of extension professionals and poultry farmers on the threat of avian influenza towards a possible outbreak in Akwa Ibom State of Nigeria. One hundred and three (103) extension officers and 43 poultry farmers were randomly selected to take part in the study. Questionnaire was used to collect data from the respondents and the data collected were analyzed with descriptive and inferential statistics. The result of the hypotheses show no significant relationship between the level of awareness of extension officers and their perception on avian influenza (r = 0.90). Similarly, there was no significant relationship between the level of awareness of poultry farmers and their perception on avian influenza (r = 0.129). Awareness campaign on avian influenza should be intensified and with more training programs for the extension officers.